Prevalence of familial autoimmune diseases in juvenile idiopathic arthritis: results from the international Pharmachild registry - Joeri W. van Straalen; Sytze de Roock; Gabriella Giancane; Ekaterina Alexeeva; Elena Koskova; Pablo Mesa-; Francesco Zulian; Adele Civino; Davide Montin; Nico M. Wulffraat; Nicolino Ruperto; Joost F. Swart; et al. (BMC, 2022)
Abstract Background Little is known about the disposition to autoimmune diseases (ADs) among children diagnosed with JIA. In this study, we provide a comprehensive overview of the prevalence of and factors associated with ADs in parents of children with juvenile idiopathic arthritis (JIA). Methods Prevalence rates of ADs and 95% Poisson confidence intervals were calculated for parents of JIA patients from the international Pharmachild registry and compared with general population prevalence rates as reported in the literature. Demographic, clinical and laboratory features were compared between JIA patients with and without a family history of AD using χ2 and Mann-Whitney U tests. Results Eight thousand six hundred seventy three patients were included and the most common familial ADs were psoriasis, autoimmune thyroid disease, rheumatoid arthritis and ankylosing spondylitis. The prevalence of several ADs was higher in parents of the included JIA patients than in the general population. Clinical Juvenile Arthritis Disease Activity Scores at study entry and last follow-up were not significantly different between patients with (n = 1231) and without a family history of AD (n = 7442). Factors associated with familial AD were older age at JIA onset (P < 0.01), Scandinavian residence (P < 0.01), enthesitis-related arthritis, psoriatic arthritis and undifferentiated arthritis (P < 0.01), ANA positivity (P = 0.03) and HLA-B27 positivity (P < 0.01). Conclusions Familial AD proves to be a risk factor for JIA development and certain diseases should therefore not be overlooked during family health history at the diagnosis stage. A family history of AD is associated with the JIA category but does not influence the severity or disease course.